3D printing of PVA/hexagonal boron nitride/bacterial cellulose composite scaffolds for bone tissue engineering. (November 2020) - Aki, Deniz; Ulag, Songul; Unal, Semra; Sengor, Mustafa; Ekren, Nazmi; Lin, Chi-Chang; Yılmazer, Hakan; Ustundag, Cem Bulent; Kalaskar, Deepak M.; Gunduz, Oguzhan
Abstract: In this study, a novel Polyvinyl Alcohol (PVA)/Hexagonal Boron Nitride (hBN)/Bacterial Cellulose (BC) composite, bone tissue scaffolds were fabricated using 3D printing technology. The printed scaffolds were characterized by fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), tensile testing, swelling behaviour, differential scanning calorimetry (DSC), and in vitro cell culture assay. Results demonstrated that bacterial cellulose addition affected the characteristic properties of the blends. Morphological studies revealed the homogenous dispersion of the bacterial cellulose within the 12 wt%PVA/0.25 wt%hBN matrix. Tensile strength of the scaffolds was decreased with the incorporation of BC and 12 wt%PVA/0.25 wt%hBN/0.5 wt%BC had the highest elongation at break value (93%). A significant increase in human osteoblast cell viability on 3D scaffolds was observed for 12 wt%PVA/0.25 wt%hBN/0.5 wt%BC. Cell morphology on composite scaffolds showed that bacterial cellulose doped scaffolds appeared to adhere to the cells. The present work deduced that bacterial cellulose doped 3D printed scaffolds with well-defined porous structures have considerable potential as a suitable tissue scaffold for bone tissue engineering (BTE). Graphical abstract: Unlabelled Image Highlights: 3D printed PVA with hexagonal boron nitride and bacterial cellulose were promising for bone tissue engineering applications. Bacterial cellulose was obtained successfully from Gluconacetobacter xylinus . Scaffolds with controlled porosity were fabricated. Additive manufacturing used for scaffold production.